Effect of calcium phosphate addition to fluoride containing dental varnishes on enamel demineralization. (September 2016) - Shen, P; Bagheri, R; Walker, GD; Yuan, Y; Stanton, DP; Reynolds, C; Reynolds, EC
Abstract: Background: The aim of this study was to evaluate the ability of calcium phosphate and fluoride containing varnishes to inhibit enamel demineralization. Methods: Six varnishes were selected for analysis: (1) Enamel Pro containing amorphous calcium phosphate; (2) Clinpro White containing functionalized tricalcium phosphate (fTCP); (3) MI Varnish containing casein phosphopeptide‐stabilized amorphous calcium phosphate (CPP‐ACP); (4) Duraphat (first no added calcium control); (5) Profluorid (second no added calcium control); and (6) placebo (no added calcium or fluoride control). Human enamel slabs (36) were each cut into half‐slabs and covered with one of the six dental varnishes to create a window. The half‐slabs were then individually immersed in a polyacrylate demineralization buffer pH 4.8 for four days at 37 °C with a change of solution each day. Mineral content was determined using transverse microradiography. Results: All fluoride‐containing varnishes significantly inhibited enamel demineralization when compared with the placebo varnish. However, out of the calcium phosphate and fluoride containing varnishes only MI Varnish, containing fluoride and CPP‐ACP was superior to the fluoride‐alone varnishes. MI Varnish also released the highest levels of calcium, phosphate and fluoride ions. Conclusions: MI Varnish containing fluoride and CPP‐ACP was superior to the other varnishes in protecting against enamel demineralization.